2014
DOI: 10.1177/1053825913518894
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Psychology and Experiential Education

Abstract: This article examines the significance of psychology to experiential education (EE) and critiques EE models that have developed in isolation from larger psychological theories and developments. Following a review of literature and current issues, select areas of psychology are explored with reference to experiential learning processes. The state of knowledge and emerging paradigms in positive psychology, self-determination theory, flow theory, and neuropsychology are explored in an effort to better understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In recent years, there has been a call for integration between the fields of experiential education and fields that share common philosophical roots, such as service-learning (Seaman & Gass, 2004) Here, researchers have suggested that unity and collaboration between the fields can provide effective reform initiatives, lead to the integration of research frameworks, enable research to be situated within a larger empirical base, and improve upon the efficacy of future education programs (Mackenzie et al, 2014;Seaman & Gass, 2004). Given that positive psychology has encompassed the study of wellbeing and positive mental states such as happiness (Lyubomirsky, 2008;Veenhoven, 2008), life satisfaction (Diener, Suh, Lucas, & Smith, 1999), and psychological strengths (Keyes, Shmotkin, & Ryff, 2002;Ryff, 1989) over the past two decades, a dearth of literature on the processes and mechanisms behind a wide variety of positive outcomes is readily available.…”
Section: Positive Psychology and Outdoor Educationmentioning
confidence: 99%
“…In recent years, there has been a call for integration between the fields of experiential education and fields that share common philosophical roots, such as service-learning (Seaman & Gass, 2004) Here, researchers have suggested that unity and collaboration between the fields can provide effective reform initiatives, lead to the integration of research frameworks, enable research to be situated within a larger empirical base, and improve upon the efficacy of future education programs (Mackenzie et al, 2014;Seaman & Gass, 2004). Given that positive psychology has encompassed the study of wellbeing and positive mental states such as happiness (Lyubomirsky, 2008;Veenhoven, 2008), life satisfaction (Diener, Suh, Lucas, & Smith, 1999), and psychological strengths (Keyes, Shmotkin, & Ryff, 2002;Ryff, 1989) over the past two decades, a dearth of literature on the processes and mechanisms behind a wide variety of positive outcomes is readily available.…”
Section: Positive Psychology and Outdoor Educationmentioning
confidence: 99%
“…The reflections by the programme coordinators showed that all of the programmes utilised the active learning approach, which emphasises active engagement by students and assumes that students take responsibility for their own learning (Healey & Jenkins, 2000; Houge Mackenzie, Son, & Hollenhorst, 2014). The implications of the pedagogical approach used within all of the programmes are seen in the structure of the sessions with the students where a seminar or workshop style of instruction is preferred.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The emphasis is on maximising the contact time between student and instructor. Within the active or experiential learning framework (Healey & Jenkins, 2000; Houge Mackenzie et al, 2014) used by the majority of course coordinators, the position of the facilitator or lecturer is seen as supporting the independent learning that the students undertake in their own time. The expectation is for students to take responsibility for their learning, while the instructors and facilitators are expected to fill the gaps in understanding that are experienced by the students.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…EE is simply defined as "challenge and experience followed by reflection leading to learning and growth" (What is Experiential Education, 2018). Mackenzie, Son & Hollenhorst (2014) contend that there is a need to strengthen Experiential Educational programs by aligning them with underlying and well-established psychological theories. They state that "EE research findings can be improved by situating them within widely accepted psychological frameworks… recognizing the psychological processes that facilitate positive program outcomes can increase efficacy for future EE programming and research" (p. 76).…”
Section: Final Underpinningsmentioning
confidence: 99%